The Use of Quizizz Application to Improve Motivation and Learning Outcomes in Science Subjects of 6th-Grade Students - Anggraini, Vina; Erviana, Vera Yuli (International Journal of Learning Reformation in Elementary Education, 2023)
The background of this research is that the motivation and learning outcomes of science learning outcomes are not yet optimal for the sixth-grade students of SD Muhammadiyah Karangwaru Yogyakarta. This happens due to the lack of teacher ability to use interactive learning media with the development of an increasingly advanced era in learning activities. This causes learning activities to become less active, forcing students to feel bored and bored when participating in learning activities in the classroom. Therefore, one of the efforts that can be used to increase students' motivation and learning outcomes is to use the Quizizz learning media. This study aims to 1) Determine the effect of using Quizizz learning media in science learning activities on student learning motivation and 2) Determine the influence of Quizizz learning media in science learning activities on student learning outcomes. This research is a quantitative type of research using an experimental research model. The technique of collecting data on students' learning motivation using a questionnaire/questionnaire and collecting data on student learning outcomes with the results of pretest and posttest tests. The population in this study were all students of class VI, consisting of classes VI A, VI B and VI C of SD Muhammadiyah Karangwaru, a total of 62 students, all of whom were used as samples. The data analysis technique used in this study was SPSS 26 For Windows with a t-test (Independent Sample T-test). The results of this study indicate that: 1) There is an influence on the use of Quizizz learning media in science learning activities for class VI SD on students' learning motivation. The percentage of the experimental class students' learning motivation showed higher results than the control class results. It can be seen that the average rate of students' learning motivation in the experimental class has increased from 72.66 to 78.53. 2) There is an influence on the use of Quizizz learning media in science learning activities for class VI SD on student learning outcomes (posttest). The percentage of experimental class students' learning outcomes increased from the pretest score, averaging 68.6 to 74.7 at the post-test.